Safety and Efficiency of Dipeptidyl Peptidase IV Inhibitors in Patients with Diabetic Kidney Disease: A Systematic Review and Meta-Analysis - Adili Tuersun, M.A.; Munire Mohetaer, M.A.; Guanxin Hou, B.A.; Gang Cheng, Ph.D (Current Therapeutic Research)
Background: To investigate the safety and efficiency of dipeptidyl peptidase-4 (DPP-4) inhibitors in patients with diabetic kidney disease. Methods: We conducted a comprehensive literature search across multiple databases, including Embase, PubMed, CNKI, and the Cochrane Central Register of Controlled Trials, from inception to January 2024. The search focused on randomized controlled trials (RCTs) that directly compared DPP-4 inhibitors with placebos or other glucose-lowering therapies. A meta-analysis was performed to pool data and quantify the therapeutic effects and safety profile of DPP-4 inhibitors in DKD. Results: Twenty-three RCTs with 16,378 participants were included. DPP-4 inhibitors significantly reduced urinary albumin-to-creatinine ratio (UACR) and HbA1c levels compared to controls (UACR: SMD -0.23, 95% CI: -0.41, -0.06; p = 0.01; HbA1c: SMD -0.32, 95% CI: -0.51, -0.14; p = 0.0006). A higher proportion of patients in the DPP-4 inhibitor group achieved at least a 30% reduction in UACR (OR = 1.73, 95% CI: 1.10, 2.73; p = 0.02). However, estimated glomerular filtration rate (eGFR) and serum creatinine (SCr) changes were similar between groups (eGFR: p = 1.00; SCr: p = 0.67). No significant differences were found in all-cause mortality (OR = 0.94, 95% CI: 0.83, 1.06; p = 0.31) or hypoglycemia risk (OR = 1.10, 95% CI: 0.80, 1.52; p = 0.54) between the DPP-4 inhibitor and control groups. Conclusions: DPP-4 inhibitors exhibit renoprotective properties, indicated by significant reductions in UACR and HbA1c levels. They do not appear to increase the risk of hypoglycemia, presenting a favorable safety profile when compared to placebo or alternative antidiabetic agents.